Measurement of tensile properties of selected rovings - Věra Kabíčková; Jakub Hájek; Jan Macháček; Eliška Kafková; Tomáš Vlach (Acta Polytechnica CTU Proceedings)
This article is focused on measuring the tensile properties of chosen fibre materials, such as flax, alkali resistant glass or viscose. All selected materials were tested both pure and impregnated using epoxy resin. In this article, the tensile strength and the Young’s modulus were observed. Young’s modulus was measured using Digital Image Correlation. The suitability of the location of small speckle pattern targets, which are used for measurements of deformations, was first verified on the viscose fiber samples. Targets were applied directly to the roving and further to the sleeves made of epoxy resin used to fix samples in the test equipment. After the evaluation, the selected location was then applied to the selected types of rovings. Finally, the measured results were compared.